Characterization of an immune-enhancing polysaccharide fraction isolated from heat-processed ginseng derived from panax ginseng c.A. meyer - Kim, Sung Jin; Shin, Myoung Sook; Kim, Minyeong; Baek, Seung Hoon; Kang, Ki Sung (Applied Sciences (Switzerland), 2021)
Panax ginseng C.A. Meyer (ginseng) has shown immune-enhancing activity in many studies. The purpose of the present study was to analyze the chemical properties of a polysaccharide fraction (SGP) purified from heat-processed ginseng and to evaluate its immune-enhancing activity using RAW264.7 macrophages. The results showed that SGP increased inducible nitric oxide synthase expression and nitric oxide production in RAW264.7 macrophages. In addition, SGP increased mRNA expression and secretion of interleukin 6 and tumor necrosis factor alpha. Immunoblotting results showed that SGP increased the phosphorylation of mitogen-activated protein kinases (MAPKs) and NF-κB subunit p65 at 500 µg/mL and 1000 µg/mL. Taken together, SGP can activate macrophages through the MAPK and NF-κB signaling pathways, and it may help maintain homeostasis during viral and bacterial infections.
Keywords: Heat-processed; Innate immune enhancing; Panax ginseng C.A. Meyer; Polysaccharide